Pineal cyst without hydrocephalus: clinical presentation and postoperative clinical course after infratentorial supracerebellar resection - El Damaty, Ahmed; Fleck, Steffen; Matthes, Marc; Baldauf, Joerg; Schroeder, Henry W. S. (World neurosurgery, 2019)
Background - Surgical indications for patients with pineal cysts are controversial. There are absolute indications such as hydrocephalus or tectal compression; otherwise, it is difficult to decide whether surgery would be beneficial when symptoms are not distinct. - Objective - We tried to clarify the indications and clinical course of patients after resection of pineal cysts without ventriculomegaly. - Methods - We reviewed our database for all patients operated on for pineal cyst without ventriculomegaly from 2003 to 2018. We studied the presenting symptoms, cyst size, surgical approach, extent of resection, and clinical and radiologic follow-up. Follow-up ranged from 3 months to 14 years (mean 3.74 years). - Results - Forty-three patients underwent surgery for pineal cyst in absence of ventriculomegaly; 36 female patients, 7 male patients, mean age 25.63 years (±10.62 years, range 4-52 years). Presenting symptoms included headache (41/43), nausea and vomiting (31/43), dizziness (19/43), visual disturbances (10/43), and sleep disturbances (8/43). Mean cyst size was 15.7 mm (±4.9 mm, range 9-27 mm). In total, 41 of 43 patients reported a good outcome, represented by a Chicago Chiari Outcome Scale score of 11 or greater and only 2 of 43 patients reported a bad outcome, defined by Chicago Chiari Outcome Scale score of 10 or less. - Conclusions - We suggest that pineal cysts without ventriculomegaly are an indication for surgery when patients present with headache and/or visual disturbances and other causes have been excluded. Resolution of symptoms and quality of life in our cohort may denote a good indication for resection. However, we must admit that there is still no evidence to recommend this technique as a treatment of headache in these patients.